Expanding the Role of Primary Care in the Prevention and Treatment of Childhood Obesity: A Review of Clinic- and Community-Based Recommendations and Interventions - Michaela Vine; Margaret B. Hargreaves; Ronette R. Briefel; Cara Orfield (Journal of Obesity)
Although pediatric providers have traditionally assessed and treated childhood obesity and associated health-related conditions in the clinic setting, there is a recognized need to expand the provider role. We reviewed the literature published from 2005 to 2012 to (1) provide examples of the spectrum of roles that primary care providers can play in the successful treatment and prevention of childhood obesity in both clinic and community settings and (2) synthesize the evidence of important characteristics, factors, or strategies in successful community-based models. The review identified 96 articles that provide evidence of how primary care providers can successfully prevent and treat childhood obesity by coordinating efforts within the primary care setting and through linkages to obesity prevention and treatment resources within the community. By aligning the most promising interventions with recommendations published over the past decade by the Institute of Medicine, the American Academy of Pediatrics, and other health organizations, we present nine areas in which providers can promote the prevention and treatment of childhood obesity through efforts in clinical and community settings: weight status assessment and monitoring, healthy lifestyle promotion, treatment, clinician skill development, clinic infrastructure development, community program referrals, community health education, multisector community initiatives, and policy advocacy.